2010
DOI: 10.1128/mcb.01370-09
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Expression of an Intronic MicroRNA and Its Myosin Host Gene by Exon Skipping

Abstract: The ancient MYH7b gene, expressed in striated muscle and brain, encodes a sarcomeric myosin and the intronic microRNA miR-499. We find that skipping of an exon introduces a premature termination codon in the transcript that downregulates MYH7b protein production without affecting microRNA expression. Among other genes, endogenous miR-499 targets the 3 untranslated region of the transcription factor Sox6, which in turn acts as a repressor of MYH7b transcriptional activity. Thus, concerted transcription and alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(149 citation statements)
references
References 46 publications
9
138
1
Order By: Relevance
“…This begs the question as to how the lineage-restricted expression of miR-499 itself is established. Previous studies in mammalian systems have shown that Mir499 transcription can be repressed by Sox6 (van Rooij et al, 2009;Bell et al, 2010), which would be consistent with slow-lineage-specific mir499 transcription being promoted by Prdm1a activity in zebrafish. To test this possibility, we analysed expression of the mir499 host gene myh7b in wild-type and prdm1a mutant embryos.…”
Section: Research Reportsupporting
confidence: 64%
See 2 more Smart Citations
“…This begs the question as to how the lineage-restricted expression of miR-499 itself is established. Previous studies in mammalian systems have shown that Mir499 transcription can be repressed by Sox6 (van Rooij et al, 2009;Bell et al, 2010), which would be consistent with slow-lineage-specific mir499 transcription being promoted by Prdm1a activity in zebrafish. To test this possibility, we analysed expression of the mir499 host gene myh7b in wild-type and prdm1a mutant embryos.…”
Section: Research Reportsupporting
confidence: 64%
“…Previous studies have implicated Mir499, a microRNA gene residing in the nineteenth intron of Myh7b, in regulating Sox6 transcript levels in mammalian myofibres, but not in direct repression of Sox6 translation (McCarthy et al, 2009;van Rooij et al, 2009;Bell et al, 2010). MicroRNAs are known to regulate both mRNA stability and translation by targeting sequences in the 3ЈUTRs of mRNAs (Huntzinger and Izaurralde, 2011).…”
Section: Hcne2:mcherry)mentioning
confidence: 99%
See 1 more Smart Citation
“…Because Myh7 and Myh7b are slow-twitch myosin fibers, these miRNAs were detected in slow-twitch muscles. Sex determining region Y-box 6 (Sox6) gene, which represses slow muscle fiber-enriched genes transcription, is a target of miR-208b and miR-499 (5,19,30). Similarly, by analysis of multiple bioinformatics algorithms, a highly conserved binding site for miR-206 is predicted in the 3'UTR of the Sox6 transcripts.…”
Section: Assessment Of Plasma Mirnas As Biomarkers In Rodent Models Omentioning
confidence: 99%
“…Emphasis would be placed on studying miRNAs with known functional roles in muscle phenotype regulation. myomiRs, a collection of miRNAs specifically expressed in muscle, have been shown to play roles in myogenesis, muscle fiber size, sarcomere organization and muscle gene expression (Ai et al, 2012;Bell et al, 2010; Callis et al, 2009;Liu et al, 2008;Mishima et al, 2009;Sokol and Ambros, 2005;van Rooij et al, 2007;van Rooij et al, 2009;Zhao et al, 2007). Electrocytes may contain a composition of myomiRs that is different from that in skeletal muscle.…”
mentioning
confidence: 99%